Waaihoek se N.G. sendinggemeente in Bloemfontein: 1891-1903 - R. M. Britz (Acta Theologica)
This article considers the early history of a unique Dutch Reformed mission congregation in the capital of the Free State Republic. Members, especially elder John Fraser of the local  “Tweetoringkerk”, initiated the establishment of a separate mission congregation in Waaihoek, at that time the non-white residential area of Bloemfontein. In terms of the Ecclesiastical Laws of the Dutch Reformed Church of the Orange Free State, this church was founded in 1891. In 1895, the Waaihoek church, which was related to the (white) Dutch Reformed congregation of Bloemfontein, obtained a religious teacher, who was eventually ordained as missionary in 1897. Tension grew within the congregation because of the influx of black Basotho people who neither understood Dutch nor had the culture of the initial “Coloured” (brown) members. Consequently, the services and the administration of the sacraments (both Baptism and Holy Communion) were held separately. The congregation experienced the Anglo-Boer War in its own way. Their perspective on the War differed from that of those belonging to the white congregation. The Waaihoek congregation had to contend with a neighbouring concentration camp for black people. Ultimately it survived the war.